How Product Quality and Price Drive Repurchase Decisions: The Mediating Role of Consumer Satisfaction - Ramadhina, Alifa; Muslikh (Research of Business and Management, 2025)
This study examines the impact of item quality and cost on repurchase decisions for L’Oréal products on Shopee, with buyer satisfaction as an intervening variable. Using purposive sampling, a non-probability sampling technique, data was collected through surveys. The study employs the Partial Least Squares Structural Equation Modeling (PLS-SEM) method for analysis. The findings indicate that: (1) Item quality has a positive and significant effect on buyer satisfaction. (2) Cost positively and significantly influences shopper satisfaction. (3) Shopper satisfaction positively impacts repurchase decisions. (4) Item quality directly influences repurchase decisions. (5) Cost does not directly affect repurchase decisions. (6) Item quality mediates the relationship between shopper satisfaction and repurchase decisions. (7) Cost also acts as a mediator between shopper satisfaction and repurchase decisions. From a managerial perspective, these findings highlight the importance of improving product quality and setting competitive prices to enhance buyer satisfaction, ultimately encouraging repeat purchases. Companies should focus on product development and strategic pricing to strengthen customer loyalty and drive sales growth.